Identifikasi Potensi Air Tanah Di Desa Latellang Kec. Patimpeng Kab. Bone Sulawesi Selatan - Noor, Moh Khaidir; Muh Yazid Amsah, La Ode; Surianti; Anna Irada La Ode Malim; Agus Margana Womal; Nor Dani (Empowerment: Jurnal Pengabdian Masyarakat, 2025)
Groundwater is water stored in layers of soil or rocks below the surface of the ground. Groundwater has an important role as a source of water for human life, especially for household needs. This community service activity aims to provide information to the community regarding the availability of groundwater potential zones and provide recommendations for the depth of groundwater drilling. The background to this activity was because there were people in Latellang Village, Patimpeng District, Kab. Bone still relies on shallow groundwater (dug wells) to meet its clean water needs. The method used is the geoelectric method where data is collected directly in the field, from the measurement data then analysis is carried out to determine the presence of groundwater potential zones in Latellang Village, Patimpeng District, Bone Regency. The results of the geoelectric measurements carried out obtained a resistivity value of 80.8 ohm.m as a layer that has the potential to be an aquifer layer with a breccia lithology type, where the porosity is high so it is good as a reservoir rock. The thickness of this layer reaches 92.7 meters starting from a depth of 5.38 to 97.7 meters.